Technical and technological analysis of individual wastewater treatment systems = Techniczna i technologiczna analiza indywidualnych mechaniczno-biologicznych oczyszczalni ścieków - Jakubaszek, Anita; Stadnik, Artur (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article characterises most frequently selected by investors individual mechanical and biological sewage treatment systems. On the basis of gathered information and technical documentation, technical and technological analysis of the devices was conducted. Assessfactors include technology, structure, workflow, control, exploitation conditions, and sewage treatment system effectiveness.
Keywords: wastewater treatment systems; individual sewage treatment systems; biological technologies; mechanical and biological treatment plants; systemy oczyszczania ścieków; indywidualne oczyszczalnie ścieków; technologia biologiczna; oczyszczalnia mechaniczno-biologiczna